2019
DOI: 10.1002/1878-0261.12522
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 expression in soft tissue sarcomas is a poor‐prognosis factor and a new potential therapeutic target

Abstract: Soft tissue sarcomas (STSs) are aggressive tumors with few efficient systemic therapies. Poly(ADP‐ribose) polymerase‐1 (PARP1) inhibitors represent an emerging therapeutic option in tumors with genomic instability. The genomics of STSs is complex in more than half of cases, suggesting a high level of inherent DNA damage and genomic instability. Thus, STSs could be efficiently targeted with PARP inhibitors. Promising preclinical results have been reported, but few data are available regarding PARP1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…In order to validate these results in an independent series of patients, we examined FGFR1 and FGFR4 mRNA expression in our pooled data set of 58 WDLPS and 218 DDLPS samples and 11 normal fat samples [ 33 ]. Their clinicopathological characteristics are summarized in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to validate these results in an independent series of patients, we examined FGFR1 and FGFR4 mRNA expression in our pooled data set of 58 WDLPS and 218 DDLPS samples and 11 normal fat samples [ 33 ]. Their clinicopathological characteristics are summarized in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…It included WDLPS/DDLPS cases from 276 patients and 11 normal fat samples. It corresponds to a sample subset included in a pooled series of 1432 primary soft tissue sarcomas that we had previously gathered from 16 public data sets [ 33 ]. All samples had been profiled using DNA microarrays or RNA Sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…PARP1 has been found over-expressed in some malignant tumors and promoting tumor metastasis in soft tissue sarcoma [41] and non-small cell lung cancer [42]. Moreover, the nuclear localization of PARP1 can affect the chemo-sensitivity of hepatocellular carcinoma to oxaliplatin [43].…”
Section: Transgelin Interacts With Parp1 In Colon Cancer Cellsmentioning
confidence: 99%
“…PARP1 has been reported to play an important role in the early development and progression of CRC [42,43]. It has also been found to promote tumor metastasis in soft tissue sarcoma [44] and non-small cell lung cancer [45]. Moreover, Dorsam et al [46] have shown that PARP1 reduced the N-nitroso compounds (NOC)-induced tumorigenesis, regulated intestinal in ammation through innate immune response and promoted colorectal tumor growth.…”
Section: Transgelin Interacts With Parp1 In Colon Cancer Cellsmentioning
confidence: 99%